2020
DOI: 10.1007/s00122-019-03517-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of wheat sensitivity to the ToxB fungal effector from Pyrenophora tritici-repentis, the causal agent of tan spot

Abstract: Key message Genetic mapping of sensitivity to the Pyrenophora tritici-repentis effector ToxB allowed development of a diagnostic genetic marker, and investigation of wheat pedigrees allowed transmission of sensitive alleles to be tracked. Abstract Tan spot, caused by the necrotrophic fungal pathogen Pyrenophora tritici-repentis, is a major disease of wheat (Triticum aestivum). Secretion of the P. tritici-repentis effector ToxB is thought to play a part in mediating infection, causing chlorosis of plant tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 78 publications
0
22
0
3
Order By: Relevance
“…For the two proteinaceous toxins, ToxA reacts with a corresponding susceptibility gene in wheat ( Tsn1 ), which makes the host sensitive to the effector [ 7 ], while the corresponding host gene for ToxB remains as yet unknown but is associated with the Tsc2 locus on chromosome 2B [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the two proteinaceous toxins, ToxA reacts with a corresponding susceptibility gene in wheat ( Tsn1 ), which makes the host sensitive to the effector [ 7 ], while the corresponding host gene for ToxB remains as yet unknown but is associated with the Tsc2 locus on chromosome 2B [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…PtrToxA is a fibronectin type III-like peptide with an arginyl-glycyl-aspartic acid motif that interacts with Tsn1, a nucleotide-binding site leucine-rich repeat (NBS-LRR) domain and a serine/threonine protein kinase (S/TPK) domain protein. PtrToxB is a cysteine rich, apoplastic toxin, that interacts with the product of the Tsc2 gene in ToxB-sensitive wheat cultivars ( Ciuffetti et al., 2010 ; Figueroa et al., 2015 ; Corsi et al., 2020 ). Several of the candidate effectors identified in the present study were reported by Guyon et al.…”
Section: Discussionmentioning
confidence: 99%
“…Different wheat MAGIC populations have been exploited to identify QTL controlling resistance against fungal diseases such as powdery mildew (caused by Blumeria graminis), STB, tan spot (caused by Pyrenophora tritici-repentis) [59,60], and Septoria leaf and glume blotch (caused by Parastagonospora nodorum) [61]. While genetic resistance to STB has been previously identified using BMWpop [60], the phenotypic response was observed under artificial inoculation.…”
Section: Introductionmentioning
confidence: 99%